Assessment of livelihood vulnerability of land-lost farmers in urban fringes: A case study of Xi'an, China. (January 2017) - Huang, Xiaojun; Huang, Xin; He, Yanbing; Yang, Xinjun
Abstract: Research on rural household livelihood vulnerability to climate change and extreme weather events (e.g., drought, flood and typhoons) has received broad attention; however, relatively few attempts have been made to assess the effects of social, economic, or spatial variation on livelihood vulnerability. With China's rapid urban expansion, many farmers in urban fringe areas are suffering great risks to their livelihoods because of land requisition. Thus, the livelihood of these land-lost farmers has become an important social issue in China. This article applies the livelihood vulnerability analytical framework to the case of land-lost farmers in the urban fringe of Xi'an who have been exposed to rapid urbanization. We developed indicators to assess the impact of exposure/sensitivity and response capacity on the livelihood vulnerability of land-lost farmers. Using a mix of qualitative and quantitative analyses, we combined data from in-person interviews and household surveys in 2015. Four types of livelihood vulnerability for land-lost households were classified: high sensitivity and high response capacity, low sensitivity and high response capacity, low sensitivity and low response capacity, and high sensitivity and low response capacity. The type of crop farmed before losing land had the greatest impact on the sensitivity of land-lost farmers, but no significant impact on response capacity. Having a commercially viable house, income diversity, educational level, land compensation, and social capital are major factors that influence the response capability of land-lost farmers. Our findings highlight the need for land-lost farmers to improve their educational level and occupational skills, and thus enhance their capacity for sustainable and diversified livelihoods. Simultaneously, local government must provide livelihood assistance in the form of employment training, improved social welfare, and limited disorderly urbanization. Highlights: Four types of livelihood vulnerability for land-lost households were classified. Type of crop farmed before land loss had greatest impact on sensitivity of farmers. Diverse income is the most important factor that influences response capacity of land-lost farmers.